2002
DOI: 10.1021/ol026007y
|View full text |Cite
|
Sign up to set email alerts
|

Peracetylated Sugar Derivatives Show High Solubility in Liquid and Supercritical Carbon Dioxide

Abstract: [structure: see text] Acetylated sugars derivatives exhibit high solubility in liquid and supercritical carbon dioxide (scCO(2)). Peracetylated sorbitol and beta-D-galactose are soluble under mild conditions in scCO(2), high pressures are required to dissolve peracetylated beta-cyclodextrin, and peracetoxyalkyl chains impart CO(2)-solubility to amides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 16 publications
1
71
0
6
Order By: Relevance
“…[6] Indeed, playing with different substituents and building polymers containing the carbonyl function has allowed tuning the solubility in CO 2 and has opened the door to a wider range of applications of this solvent in green processes. Among the carbonyl-based, CO 2 -phile materials that have been developed are functionalized silicones, [7] diglycolic acid esters, [8] poly(ether-carbonate) copolymers, [9] sugar [10] and amide [11,12] derivatives. Theoretical studies on model systems have been carried out to analyze the interactions of CO 2 with carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Indeed, playing with different substituents and building polymers containing the carbonyl function has allowed tuning the solubility in CO 2 and has opened the door to a wider range of applications of this solvent in green processes. Among the carbonyl-based, CO 2 -phile materials that have been developed are functionalized silicones, [7] diglycolic acid esters, [8] poly(ether-carbonate) copolymers, [9] sugar [10] and amide [11,12] derivatives. Theoretical studies on model systems have been carried out to analyze the interactions of CO 2 with carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups [10,61,116,[118][119][120][121][122][123][124][125][126] have sought to find non-fuorinated compounds that would be soluble in CO 2 in the hopes of creating non-fluorinated polymers as well as surfactants where the latter could be used to form microemulsions in CO 2 . Research has shown that branched, methylated, and stubby surfactants can be used to form micelles in supercritical CO 2 , because of higher tail solvation and smaller tail-tail interactions [44,45,61,127].…”
Section: Non-fluorous Thiols Resultsmentioning
confidence: 99%
“…Acetylated sugars, such as per-acetylated glucose and galactose, [47] sorbitol, [48] maltose [49] and cyclodextrins, [50] have been shown to dissolve in CO 2 at low pressures up to 10-50 wt%. The high degree of CO 2 solubility has been attributed to a favorable two-point interaction between …”
Section: Per-acetylated Sugarsmentioning
confidence: 99%
“…[196] The first difficulty in this area arises from the fact that native cyclodextrins are insoluble in scCO 2 ,m eaning that functionalization of the glycosidic OH groupsi sn ecessary.T he idea to construct scCO 2 soluble compounds with multiple ester functionalities througha cetylationo fo ligo-hydroxy derivatives was proposed by Beckmana nd co-workers. [193] Peracetylated sugars derivatives exhibit highs olubility in scCO 2 , [132,193] as well as peracetylated b-cyclodextrin, [193] although the latter required higher pressures to dissolve.…”
Section: Solubilizers and Host-guest Chemistrymentioning
confidence: 99%